Muhammad Abduh's Qur'anic Interpretation Of Jihad: Implementation And Challenges In Modern Indonesian Society - Abdul Rohman; Mega Rustiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2024)
Muhammad Abduh is a modern mufassir whose thoughts are widely studied by scholars, one of which is about the verse of jihad. Abduh's ideas about the interpretation of the verse of jihad have inspired the birth of new thoughts that are more accommodating to the times. The purpose of this paper is to explore Abduh's thoughts on jihad in the Qur'an; implement and analyze the challenges of Abduh's jihad interpretation for modern Indonesian society; and analyze the positive and negative impacts of the implementation offer. The method used is library research with a content analysis approach. The results revealed that Abduh understood jihad was not limited to military and war aspects, spiritual, moral, social, and educational struggles also included the meaning of jihad. Jihad is also understood as a continuous effort to improve oneself and society, uphold justice, and advance science and social reform; the implementation of Abduh's meaning of Jihad is very relevant and in line with the needs of a plural and dynamic Indonesian society. By integrating education, dialog, and active involvement from all components of society, it can encourage the creation of a more just, peaceful, and advanced society. The challenge is that there is resistance and rejection from traditional circles that hold fast to old thinking; the positive impact of Abduh's thinking is to encourage the constructive contribution of Muslims in various aspects of life and inspire a peaceful and progressive renewal movement. Meanwhile, the negative impact is the potential for internal conflict, because his offer of thought will face the traditionalist thinking adopted by most Indonesians.